2004
DOI: 10.1097/01.ta.0000087644.90727.df
|View full text |Cite
|
Sign up to set email alerts
|

Management of Blunt Major Pancreatic Injury

Abstract: The complication rate for our cases of blunt major pancreatic injury was high (62.2%), especially when treatment was delayed more than 24 hours; the same result was also noted for cases transferred from other institutions. Distal pancreatectomy with spleen preservation had a lower complication rate (22.2%) compared with other procedures and is suggested for grade III and grade IV injuries. Magnetic resonance pancreatography was unreliable early after injury but was effective in the chronic stage. Although panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
189
2
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(200 citation statements)
references
References 15 publications
1
189
2
8
Order By: Relevance
“…The spectrum of injuries ranges from minor contusions to massive disruption of the pancreatic. 5 In addition, pancreatic injuries rarely occur by themselves and are often associated with other intra-abdominal injuries, such as those of the liver, duodenum and major vessels. 6 Due to retroperitoneal location of the organ, symptoms and signs of pancreatic trauma are subtle making diagnosis more difficult and easily missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectrum of injuries ranges from minor contusions to massive disruption of the pancreatic. 5 In addition, pancreatic injuries rarely occur by themselves and are often associated with other intra-abdominal injuries, such as those of the liver, duodenum and major vessels. 6 Due to retroperitoneal location of the organ, symptoms and signs of pancreatic trauma are subtle making diagnosis more difficult and easily missed.…”
Section: Discussionmentioning
confidence: 99%
“…5 A study from Taiwan showed that Distal Pancreatectomy is a superior operative treatment for distal injuries when compared to pancreaticojejunostomy, which had a high complication rate of 60% due to anastomotic leakage. 5 While an attempt at splenic preservation in stable patients is an option, this task IJBAR (2013) 04 (08) www.ssjournals.com too time-consuming with no proven benefit in the adult trauma setting. In addition, the extensive inflammation encountered in cases of delayed treatment, makes this even more difficult and is a commonly cited reason for performing splenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its diagnosis can be difficult; physical signs may be poor and laboratory findings nonspecific [1] , resulting in delayed treatment [3] . In many instances, the injury only becomes apparent after the development of complications [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, the management of these kinds of injuries is not easy and few surgeons and institutes have the necessary experience [1] . Several treatment modalities have been described, from non-surgical to open drainage and even duodenopancreatectomy [3] , depending on the grade of the lesion. Major duct injury is the most important factor related to the outcome in these patients [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation